Microchannels: High‐Aspect‐Ratio Parallel‐Plate Microchannels Applicable to Kinetic Analysis of Chemical Vapor Deposition (Adv. Mater. Interfaces 16/2016). Issue 16 (August 2016) - Shima, Kohei; Funato, Yuichi; Sugiura, Hidetoshi; Sato, Noboru; Fukushima, Yasuyuki; Momose, Takeshi; Shimogaki, Yukihiro
Abstract : Kohei Shima and co‐workers develop a very deep microchannel with aspect ratio ≥ 1000:1 as a test structure for kinetic analysis and process development of chemical vapor deposition (CVD) in article 1600254. When CVD is conducted into the microchannel, the sticking probability of film‐forming species can be detected in the range from 1 down to the order of 10 −7, by analyzing the film‐thickness gradient.